Entrepreneurial Competencies of Accountancy, Business, and Management Students in a Private Institution - Lorelie Buitrago; Mark Anthony Polinar; Alexander Franco Delantar; John Lemuel Buntigao (Philippine Association of Institutions for Research, Inc., 2022)
Entrepreneurial competencies are considered a vital piece for aspiring entrepreneurs to pursue entrepreneurial ventures. The research aimed to examine the personal entrepreneurial competencies scores of accountancy, business, and management (ABM) students in a private institution. A quantitative method engaging in descriptive research was employed in the study. The study utilized Slovin's formula, with 187 ABM students responding. The data were analyzed using mean and ranking. The findings revealed that goal-setting and information-seeking garnered high scores and were rated first and second, respectively, with an interpretation of 'strong traits' and their strengths among the identified entrepreneurial competencies. Persuasion and networking and risk-taking obtained moderate scores and were ranked 9th and 10th, respectively, and accordingly labeled as inferior characteristics. The researchers concluded that a plethora of inside and outside-of-school activities related to entrepreneurship could enhance the information-seeking skills of students. It was also determined that students' self-awareness should be strengthened since taking risks is a key component of being a successful entrepreneur. Furthermore, the study suggested that increasing entrepreneurial activities both within and outside the campus will be valuable to ABM students in developing entrepreneurial competencies, particularly for characteristics belonging to the moderate level.